Aesthetic resources in rehabilitation with implant-supported restoration in the anterior region: a clinical case - Paulo Roberto R. Ventura; Adalberto Bastos Vasconcelos (Universidade Estadual de Campinas, 2016)
Achieving aesthetic satisfaction in anterior teeth rehabilitation is a constant challenge to clinicians. Modern implantology is an invaluable tool to replace missing teeth; however, it requires carefully determined steps in each rehabilitation stage, from implant placement of the implant-supported crown. This article aims at reporting the several resources employed in a clinical case that should always be used in rehabilitation with single implant-supported crowns in the maxillary anterior area